2009
DOI: 10.1038/ijo.2009.253
|View full text |Cite
|
Sign up to set email alerts
|

Peripherally acting CB1-receptor antagonist: the relative importance of central and peripheral CB1 receptors in adiposity control

Abstract: Objective: To investigate whether drugs targeting peripheral cannabinoid-1 (CB1) receptor ameliorate adiposity comparable to central CB1-receptor antagonist or not. Measurements: Receptor binding assay and functional assay in vitro. Pharmacokinetic parameters in mice, brain uptake clearance of compounds in rats and antagonism on the CB1-agonist-induced hypothermia in mice. Diet consumption, body weight changes, hepatic gene expression of sterol-regulatory element-binding protein-1 (SREBP-1) and plasma/tissue c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 32 publications
4
37
0
2
Order By: Relevance
“…The previously published, peripherally restricted compound URB447 has approximately 100 times lower CB 1 R affinity (IC 50 , 313 nM) and lacks CB 1 /CB 2 selectivity (51), and another recently published compound with reduced brain penetrance has similarly low CB 1 R affinity (159 nM) (52). An article describing another peripherally restricted CB 1 R antagonist with nanomolar potency and a high degree of selectivity for CB 1 over CB 2 receptors appeared after the present study had been submitted for publication.…”
Section: Figurementioning
confidence: 99%
“…The previously published, peripherally restricted compound URB447 has approximately 100 times lower CB 1 R affinity (IC 50 , 313 nM) and lacks CB 1 /CB 2 selectivity (51), and another recently published compound with reduced brain penetrance has similarly low CB 1 R affinity (159 nM) (52). An article describing another peripherally restricted CB 1 R antagonist with nanomolar potency and a high degree of selectivity for CB 1 over CB 2 receptors appeared after the present study had been submitted for publication.…”
Section: Figurementioning
confidence: 99%
“…A number of studies have demonstrated that CB 1 antagonists and inverse agonists are an effective anti-obesity therapeutic (Van Gaal et al 2005, Janiak et al 2007, Rosenstock et al 2008, Nam et al 2012, Tam et al 2012. However, characterisation of the physiological effects of CB 1 antagonism in the periphery is limited outside of metabolically active tissues (Sink et al 2008, Son et al 2010, Merroun et al 2013. Therefore, it is essential to determine whether antagonism of CB 1 in the periphery alters disease progression in other tissues to ensure a full investigation of its potential as a therapeutic target.…”
Section: Introductionmentioning
confidence: 99%
“…L'aumento de novo della lipogenesi epatica, è stata documentata nel topo DIO (62,63), così come nei soggetti con NAFLD (64,65), e può essere mediata dagli endocannabinoidi. Infatti, in studi condotti nei roditori, l'espressione del gene lipogenico e il tasso di lipogenesi epatica de novo, risultavano aumentati dagli agonisti CB 1 e diminuiti dagli antagonisti (66,67,68,69). Una dieta ricca di grassi aumenta l'espressione epatica dei CB 1 (70) e i livelli di AEA.…”
Section: Endocannabinoidi E Fibrosi Epaticaunclassified